Modern classroom assessment - Frey, Bruce B. (SAGE, 2014)
Modern Classroom Assessment offers an applied, student-centered guide to the major research-based approaches to assessment in today's modern classroom. Rather than simply list basic assessment formats with a few examples, as many textbooks do, award-winning professor and scholar Bruce Frey's book fully explores all five key approaches for teacher-designed assessment--Traditional Paper-and-Pencil, Performance-Based Assessment, Formative Assessment, Universal Test Design, and Authentic Assessment --while making abstract concepts and guidelines clear with hundreds of real-world illustrations and examples of what actual teachers do. Offering a variety of engaging learning tools and realistic stories from the classroom, this text will give any reader a strong foundation for designing modern assessments in their own classrooms